(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
our study aims To apply 5G technology in the fields of information technology, where the study includes the application of 5G technology in information technology applications and artificial intelligence applications, where an algorithm is created to determine the extent of development taking place in developing programs over the Internet and managing them remotely and controlling them as a result of the speed of 5G technology, which is equivalent to hundreds of times from previous technologies (4G / 3G / 2G) Heading over the advantages and disadvantages of using 5G technology, through the use of the algorithm, the extent of development is evaluated and the use of this evaluation in developing other areas of technology to create a technological environment that can be controlled remotely that carries out all electronic governance activities as well as multiple areas of life